Diversification of deermice (Rodentia: genus Peromyscus) at their north‐western range limit: genetic consequences of refugial and island isolation. (28th April 2017) - Sawyer, Yadéeh E.; Flamme, Melanie J.; Jung, Thomas S.; MacDonald, Stephen O.; Cook, Joseph A.
Abstract: Aim: We surveyed the genetic variability of deermice (genus Peromyscus ) at the north‐western edge of their range to test for occupancy in multiple, hypothesized ice‐free regions during the late Pleistocene and explore post‐glacial dynamics. Location: North‐western North America. Methods: We used sequences from four independent nuclear and mitochondrial loci from 341 specimens of Peromyscus maniculatus, Peromyscus keeni and Peromyscus sp. (Yukon) to assess species limits, population structure, and demographical change as a result of historical climate change, using a Bayesian approach. Species distribution models were built inMaxEnt to explore the niche overlap amongst genetically distinct species. Results: Divergence amongst three lineages began before the last interglacial, and each shows signs of post‐glacial expansion. Multilocus species trees strongly support P. keeni and Peromyscus sp. (Yukon) as independent from P. maniculatus . Substantial substructure was observed for P. keeni across the fragmented Alexander Archipelago. Northern lineages or clades ( Peromyscus sp. and P. keeni ) differed in potential ecological distributions. Main conclusions: At the extreme north‐western range of deermice in North America, three distinct lineages persist reflecting divergence in at least three ice‐free regions [Beringia, Coastal (near Southeast Alaska) and Southern Continental] throughout the latest Pleistocene glacial cycles. Although spatially proximate in Yukon, no locations were identified where these lineages are in contact. Further, west along the Pacific Coast, P. keeni is widespread across the complex landscape of Southeast Alaska, yet there is limited contemporary gene flow amongst island populations, a finding consistent with the barriers produced by rising sea levels at the end of the Last Glacial Maximum.